2016
DOI: 10.1111/jch.12783
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension and Clinical Outcomes of Patients With Gastrointestinal Submucosal Vascular (Dieulafoy) Lesional Hemorrhage

Abstract: Dieulafoy lesions are submucosal arteries found in the stomach and some other parts of the gastrointestinal (GI) tracts that can cause massive emergency GI bleeding after penetration of the mucosa over time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
0
2
0
1
Order By: Relevance
“…It has since been reduced to 4.4–8% with the advancement of non-invasive investigation modalities in addition to increased clinical awareness and surgical expertise [ 2 , 9 , 10 ]. Interestingly, 1 study examined the clinical outcomes of patients with hyper-tension who had a GI bleed due to DL, and concluded that there was an increase in mortality and morbidity rates in patients with hypertension compared to normotensive patients [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has since been reduced to 4.4–8% with the advancement of non-invasive investigation modalities in addition to increased clinical awareness and surgical expertise [ 2 , 9 , 10 ]. Interestingly, 1 study examined the clinical outcomes of patients with hyper-tension who had a GI bleed due to DL, and concluded that there was an increase in mortality and morbidity rates in patients with hypertension compared to normotensive patients [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Este paciente no cumple con los factores de riesgo en dicho estudio, puesto que se trata de un paciente joven y normotenso, lo cual apunta a un mejor pronóstico. Posterior al control del sangrado, los pacientes con lesiones de Dieulafoy tienden a reducir significativamente sus tasas de mortalidad 17 . Probablemente, los factores cardiovasculares puedan contribuir con el remodelamiento de estas lesiones y el riesgo de resangrado.…”
Section: Discussionunclassified
“…Chronic alcohol drinking and antiplatelet drugs intake are possible for intervening factors that may contribute to Dieulafoy's lesion formation, with an Odds Ratio of 3,9 (1,6-9,5 CI 95%) and 2,8 (1,2-6,2 CI 95%), respectively [5]. It is of note that hypertensive patients may experience high morbidity and mortality rates [9].…”
Section: Discussionmentioning
confidence: 99%